Three-dimensional superhydrophobic copper 7, 7, 8, 8-tetracyanoquinodimethane biointerfaces with the capability of high adhesion of osteoblasts. Issue 6 (26th January 2016) - Zhou, Jie; Fan, Jun-Bing; Nie, Qiong; Wang, Shutao
Abstract : A three-dimensional superhydrophobic copper 7, 7, 8, 8-tetracyanoquinodimethane (CuTCNQ) nanowire array with the capability of very high adhesion of osteoblasts was demonstrated. Abstract : A three-dimensional superhydrophobic copper 7, 7, 8, 8-tetracyanoquinodimethane (CuTCNQ) nanowire array with the capability of high adhesion of osteoblasts was demonstrated. The CuTCNQ nanowire array was constructed by using a combined vapor deposition technique. The superhydrophobic nanowire array exhibited very high adhesion of osteoblasts, indicating that the CuTCNQ nanowire array was a good biointerface.